IMPROVING STUDENTS READING COMPREHENSION THROUGH THE APPLICATION OF LEARNING CELL TECHNIQUE ( A Collaborative Classroom Action Research to the first Year Students of SMA Negeri 2 Kuta Makmur): IMPROVING STUDENTS READING COMPREHENSION THROUGH THE APPLICATION OF LEARNING CELL TECHNIQUE ( A Collaborative Classroom Action Research to the first Year Students of SMA Negeri 2 Kuta Makmur) - Nurafni; Iswadi (Journal of English Education and Social Science, 2021)
This thesis entiled Improving Students’ Reading Comprehension Throught the application of learning Cell Technique (A Collaborative Classroom Action Research to the first Year Student of SMA Negeri 2 Kutamakmur). The problem of this research are: 1) How does Learning Cell Technique improved the students’ reading ability in reading comprehension? And(2) how do the students’ respond toward the implementation Learning Cell Technique to the first year students’ of SMAN 2 Kuta Makmur?. The purpose of this research are: 1) To improve students’ reading comprehension to the first year students’ of SMAN 2 Kuta Makmur by using Learning Cell Technique. 2) To know the students response toward the implementation of Learning Cell Technique in teaching reading. To respond the research questions, the researcher used the collaborative classroom action research as the methodology of the research. Then the researcher did the collaboration with englis teacher to do the research. The setting of this research was SMAN 2 Kuta Makmur.